Chronic Inflammatory Demyelinating Polyneuropathy: Update on Diagnosis and Treatment - Jin Jun Luo; Xiaohong Si (Journal of Clinical Neuromuscular Disease, 2026)
Abstract Chronic inflammatory demyelinating polyneuropathy (CIDP) is an acquired immune-mediated neuropathy characterized by progressive or relapsing weakness and sensory loss because of demyelination of peripheral nerves. CIDP has a higher prevalence in men and older adults. Immunopathogenesis involves both cellular and humoral mechanisms, including autoreactive T cells and macrophage-mediated demyelination. Typical CIDP presents with symmetric sensorimotor deficits, whereas atypical variants such as distal acquired demyelinating symmetric neuropathy, Lewis–Sumner syndrome, and motor- or sensory-predominant forms pose diagnostic challenges. Corticosteroids, intravenous immunoglobulin, and plasma exchange remain first-line treatments, although antibody-mediated subtypes often respond better to B-cell–directed therapy. The newly FDA-approved FcRn antagonist, efgartigimod alfa, provides a targeted option for adults with refractory CIDP. Accurate recognition of atypical and antibody-associated forms is essential for optimizing individualized management and improving outcomes.